Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

Diagnostic imaging in cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias Martin; Schwarz, Marc; Dörfler, Arnd; Budinsky, Lubos; Heß, Andreas; Schmidt, Wolfgang; Jurgons, Roland; Alexiou, Christoph (Springer Proceedings in Physics, 2012)
The unfavorable application-to-tumor-dose-ratio is a drawback of conventional systemic chemotherapy, implying an often insufficient drug dose in the tumor being associated with severe side effects for the patient. The use of chemotherapeutics bound to magnetic nanoparticles offers several advantages. On the one hand it is possible to concentrate the chemotherapeutics in the tumor region by the use of magnetic fields, like it is done in Magnetic Drug Targeting (MDT). On the other hand magnetic particles can serve as contrast agent for magnetic resonance imaging (MRI) that is bound to the therapeutics. Hence, the particles possibly are opening an insight into drug distribution in the tumor region directly after administration. Another important factor for a successful MDT-application is detailed knowledge about tumor vascularization. In this pilot study we investigated vascularization and size of an tumor in an experimental in vivo tumor model via flat-panel angiography and DYNA-CT before MDT and the particle distribution with MRI after MDT. We could show that the tumor could be displayed by MRI and DYNA-CT before and after MDT. Flat panel angiography revealed clearly the pathological tumor vascularization before MDT, while MRI imaging afterwards displayed the tumor as well as the particle distribution in the tumor.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Magnetic Nanoparticles; Tumor Region; Magnetic Resonance Imaging Imaging; Signal Extinction; Left Hind Limb

In-Vivo Imaging of Cell Migration Using Contrast Enhanced MRI and SVM Based Post-Processing - Weis, Christian; Heß, Andreas; Budinsky, Lubos; Fabry, Ben (PLoS ONE, 2015)